Pelatihan dan Implementasi P.O.S. sebagai media penjualan pada Toko Queen vape store - trisyawal, Revanzatrisyawal (ABDIMAS : Jurnal Pengabdian Masyarakat, 2023)
Queen vape store is a shop that provides electronic goods such as electronic cigarettes. This business offers a variety of products ranging from liquid, cotton, mod and so on. This POS application is implemented at the Queen Vape Store which aims to record the results of sales at the store. For current developments, the Queen Vape Store still uses a direct system when you want to buy goods at the Queen Vape Store. Therefore, the Queen Vape Store must require a web-based application to help the process of sending product data to the store. Therefore, in this activity I developed and implemented a POS application so that it becomes more developed and useful for this Queen Shop. By creating this POS application, it is hoped that it can increase sales at the Queen Vape Store.